DOES MATERNAL PRE-PREGNANCY UNDERWEIGHT AFFECT PREGNANCY OUTCOMES IN SINGLETON PREGNANCIES? OUR EXPERIENCE AT A TERTIARY CARE CENTER IN NORTH KERALA - TRIVIKRAMA, HEERA SHENOY; KRISHNAN, REMASH; VK, CHELLAMMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: This research was aimed at analyzing the burden of maternal pre-pregnancy underweight and their effects on pregnancy outcomes in a tertiary care center in North Kerala. Methods: Based on maternal body mass index (BMI) calculated from the pregnant women’s reported height and pre-pregnancy weight, all pregnant women were divided into two groups. Underweight pregnant women with a BMI <18.5 kg/m2 at the time of conception formed group A (n=44) and women with a normal weight at conception (BMI between 18.5 and ≤24.9 kg/m2) formed Group B (n=155). Results: Underweight women had two fold more chances of delivering an low birth weight infant. (AOR 2.2, 95% CI, 1.12 3–4.475). Being underweight did not influence any other maternal or perinatal outcomes and there was rare incidence of gestational diabetes mellitus (OR, 0.937; (95% CI, 0.4– 2.29), pregnancy-induced hypertension (OR, 0.970; 95% CI, 0.2–2.9). Conclusions: Pre-conception counseling for underweight women, emphasizing the importance of proper physical activity and healthy eating to gain adequate weight in antenatal period can help avert pre-term deliveries with healthy neonates of normal birth weight.